THE CONDITIONS AND OPPORTUNITIES FOR TEACHERS’ PROFESSIONAL ADAPTATION AND CAREER IN SCHOOLS OF LATVIA AND LITHUANIA - Melnikova, Julija; Zaščerinska, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article highlights the modern notion of career and explores the salient factors, influencing teachers’ professional development and career opportunities in today’s secondary schools in Latvia and Lithuania. The implications of empirical research on the peculiarities of teachers’ as young specialists’ adaptation and it influencing factors are presented. The contradictory views on the problems of professional adaptation, expressed by two groups of respondents - school heads and young specialists - are analyzed. The article examines opinion of teachers, who have different work experience and professional category, on the topic of career development opportunities. The article also presents the empirical evidence on the question: what is the role of school heads (principal and deputy heads) in the aspect of optimization of teachers’ professional career. Moreover, the recommendations for high schools on how to optimize the teaching-learning process in order to ensure successful start of teachers’ pedagogical career are provided.